DIETARY REFERENCE INTAKES FOR THE EVALUATION AND PLANNING OF DIETS FOR CHILDREN AGED ONE TO EIGHT YEARS - Vieira, Marta N. C. M.; Japur, Camila C.; Resende, Cristina M. M.; Monteiro, Jacqueline P. (Medicina (Ribeirao Preto), 2008)
Dietary Reference Intakes (DRIs) have been developed in order to help dietary planning and the assessment of nutrient intake for individuals and populations. These values were proposed in the late nineties to replace the recommended daily allowances (RDAs), innovating and creating new concepts of dietary planning and assessment due to the recently updated information about nutrient requirements, the establishment of maximum intake levels in need to include the concept of risk-reduction of chronic-degenerative diseases, and a subdivision within each age range due to the different nutrient requirements in each stage of life. Considering the food consumption assessment important in full-range attention to the children’s health, and enabling funds to health professionals in nutritional monitoring and diagnosis, the main objective of the current study was to present, in a practice way, the nutritional recommendations and their applications for children aged 1 to 8 years old, based on the DRIs Methodology.